SOCIO-PSYCHOLOGICAL ASPECTS OF THE DEVELOPMENT OF PERSONNEL POTENTIAL OF AGRARIAN ENTERPRISES - OSTAKHOV, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The topicality of the topic in modern Ukraine is due to several reasons related to the general specificity of the agrarian sector and the new challenges faced by enterprises in the conditions of crisis and martial law.Ukraine is one of the leading agricultural countries in the world, and agriculture occupies a central place in its economy. The country's internal food security and export potential depend on the efficiency of agricultural enterprises.Many scientific works have reflected various aspects of the study of the problems of formation and development of the enterprise's personnel potential and its qualitative characteristics. However, the social and psychological aspects of the development of the personnel potential of agrarian enterprises in modern crisis conditions, in general, remain insufficiently disclosed and require further research.The article's purpose is to study the socio-psychological aspects of the development of personnel potential in agrarian enterprises.It has been proven that crisis support for an agricultural enterprise's personnel under martial law in Ukraine is extremely important for ensuring stable work, psychological stability of employees, and maintenance of production processes. During this period, agricultural enterprises' employees face numerous challenges, including physical and emotional stress, the need to adapt to changes in working conditions, and threats to life.It is emphasized that the socio-psychological aspects of the development of personnel potential of agrarian enterprises become especially relevant in the constant changes and challenges related to economic conditions and the war in Ukraine. Ensuring the stability of employees and their professional development and maintaining the emotional and social climate in the team are critical factors for enterprises' long-term success.Attention was focused on the fact that investments in personnel potential will help the agricultural sector maintain competitiveness and remain an essential part of the country's economy.
Keywords: agricultural enterprise; crisis conditions; motivation; partnership; psychological support; development of personnel potential; social projects